مهند عبد الحسين عبود تاثير مسافات مختلفه بين الجور في بعض صفات النمو وحاصل الحبوب ومكوناته لصنفين من الذرة البيضاء Sorghum bicolor L. moench - مهند عبد الحسين (University of Thi-Qar Journal of Science, 2019)
A field experiment was conducted at al Qurna which is located north of Basrah Governorate at autumn growing season of 2008 to study the effect of four planting spaces (10,15,20,25cm) and tow sorghum cultivars (Inkath and Kafir-2) on yield and its components . The experimental design was a factorial 4x2 with three replication in randomize complete block design. The results showed that there was a significant effect for cultivars and Planting spaces on all agronomic characteristics (days from planting to 50%flowering, plants height, stem diameter, leaf area index, 1000 grain weigh and grains pear head),grain yield and protein. Kafai-2 was the highest grain yield and protein (3.65T/ha and 10.00% respectively).The space 15 cm had the highest grain yield (4.25 T/ha) but the spaces 25 cm produced higher grain protean (10.40%) .The results showed significant interaction between cultivars x planting distance for all agronomic characteristics except stem diameter and the variety Kafer-2 with 15 cm spaces produce higher grain yield (4.70 t/ha) and in 10 cm produce higher grain protean (11.10%).